Association between residual cholesterol and sarcopenia in American adults - Li, Jianzhao; Lin, Yuning (Frontiers in Endocrinology, 2024)
Background Remnant cholesterol (RC) is a novel lipid metabolism indicator; however, its relationship with sarcopenia has not been clearly established. This study was conducted to explore the association between RC and sarcopenia. Methods An analysis was performed utilizing cross-sectional data from the NHANES 2011–2018. The variable RC was subjected to a logarithmic transformation to address its skewness. Logistic regression studies were conducted to examine the association between RC and sarcopenia. This study used restricted cubic spline (RCS) and threshold saturation techniques to investigate nonlinear connections. Subgroup, sensitivity, and additional analyses were performed to assess the robustness and validity of the findings. Results The study included 4636 participants. Participants with sarcopenia had significantly higher RC levels. Logistic regression demonstrated a substantial positive association between the prevalence of sarcopenia and log RC (OR=1.69, 95% CI=1.32-2.17). RCS analysis revealed a nonlinear relationship, identifying a threshold at RC=25. When the RC is below this threshold, every one-unit increase in RC increases the chance of sarcopenia by 7% (OR=1.07, 95% CI=1.04-1.10); above this threshold, changes in RC were not significant. Subgroup analysis confirmed that RC was an independent risk factor for sarcopenia. The sensitivity and supplementary analyses supported the main findings. Conclusion This study demonstrates a significant positive association between RC levels and the prevalence of sarcopenia in U.S. adults, offering novel evidence that RC may serve as a valuable indicator for sarcopenia assessment.